Waking up white : and finding myself in the story of race - Irving, Debby (2014)
For twenty-five years, Debby Irving sensed inexplicable racial tensions in her personal and professional relationships. As a colleague and neighbor, she worried about offending people she dearly wanted to befriend. As an arts administrator, she didn't understand why her diversity efforts lacked traction. As a teacher, she found her best efforts to reach out to students and families of color left her wondering what she was missing. Then, in 2009, one "aha!" moment launched an adventure of discovery and insight that drastically shifted her worldview and upended her life plan. In Waking Up White, Irving tells her often cringe-worthy story with such openness that readers will turn every page rooting for her-and ultimately for all of us.
Includes bibliographical references.
18+
Keywords: Racism -- United States; Whites -- United States -- Social conditions; United States -- Race relations